Pengaruh Kinerja Lingkungan dan Profitabilitas terhadap Corporate Social Responsibility Disclosure dalam Laporan Tahunan Perusahaan - Halmawati, Halmawati; Oktalia, Dwi (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2015)
The aim of this study is to examine the effect of environmental performance and profitability to corporate social responsibility disclosure. Environmental performance was measured using PROPER rate and disclosed in corporate annual reports. Profitability was measured using Return On Assets (ROA). Corporate Social Responsibility Disclosure was measured using Corporate Social Responsibility Disclosure Index (CSRDI). The data used in this study are secondary data from 26 go public company listed in Indonesian Stock Exchange during the 4 years from 2009 to 2012. Hypothesis testing is done by using of the multiple linear regression analysis. The result show that environmrntal performance have no effect on Corporate Social Responsibility Disclosure. And, profitability have no effect on Corporate Social Responsibility Disclosure.